Corporate Social Responsibility And Islamic Business Organizations: A Proposed Model - Rusnah Muhamad; Mohd Rizal Muwazir (Tazkia Islamic Finance and Business Review, 2008)
The issue of corporate social responsibility (CSR) has been of growing concern among business communities in recent years. Various corporate leaders maintain that business is considered to contribute fully to the society if it is effi cient, profi table and socially responsible. Islam is considered as addin (a way of life), thus, providing comprehensive guidelines in every aspects of the believers’ life. It is the aim of this paper to propose an Islamic model of corporate social responsibility based on human relationships with the God (hablun min’Allah); with other fellow human being (hablun min’an-nas) and with the environment.Keywords : Corporate Social Responsibility, Islamic Business Organization